“What’s wrong with the seed?” A comparative examination of an empowering community-centered approach to recovery in community mental health - Monteiro, Maria Fátima Jorge (2016)
This cross-sectional group comparison aimed to examine whether personal empowerment, recovery and community integration were associated with the individual's participation in an empowering community-centered model of intervention. Ninety-three participants from an empowering community-centered community mental health organization were compared with a matched group of individuals from standard interventions of four equivalent organizations. Results showed that participants taking advantage of the empowering community-centered approach were more involved in high recovery-oriented programs; and attained higher levels of personal goals and hope, empowerment, and of community integration. An involvement in high recovery-oriented programs (supported employment or independent housing) revealed improved outcomes for the individual. In conclusion, the findings suggested a transformative impact of the empowering community-centered model both at the individual and the program level by altering the resource accessibility and social conditions for people who experience mental illness. The implications of findings for transforming community mental health practice are discussed in detail.